The many faces of ubiquitinated histone H2A: insights from the DUBs - Vissers, Joseph HA; Nicassio, Francesco; van Lohuizen, Maarten; Di Fiore, Pier Paolo; Citterio, Elisabetta (Cell division, 2008)
Monoubiquitination of H2A is a major histone modification in mammalian cells. Understanding how monoubiquitinated H2A (uH2A) regulates DNA-based processes in the context of chromatin is a challenging question. Work in the past years linked uH2A to transcriptional repression by the Polycomb group proteins of developmental regulators. Recently, a number of mammalian deubiquitinating enzymes (DUBs) that catalyze the removal of ubiquitin from H2A have been discovered. These studies provide convincing evidence that H2A deubiquitination is connected with gene activation. In addition, uH2A regulatory enzymes have crucial roles in the cellular response to DNA damage and in cell cycle progression. In this review we will discuss new insights into uH2A biology, with emphasis on the H2A DUBs.